Surgical Treatment of Tracheal Lipoma after Multiple Bronchoscopy Interventions and Placements of a Tracheal Stent - Zhang, Xiaoming; Ji, Tao; Yang, Longhai; Liu, Yi; Lin, Hongsheng; Pan, Huiyu; Zhou, Zizi (The Thoracic and Cardiovascular Surgeon Reports, 2019)
Background The majority of adult primary tracheal tumors are malignant; however, as one type of benign tumors, lipoma is extremely uncommon.Case Description We report a case where lipoma was first misdiagnosed as bronchial asthma, followed by sudden aggravation of dyspnea after trauma, and computed tomography (CT) examination of the neck and chest confirmed a tracheal tumor. Through multiple bronchoscopy interventions and placements of a tracheal stent, little therapeutic benefit was discovered, and resection of the tracheal tumor combined with tracheal end-to-end anastomosis was performed to ultimately achieve a cure.Conclusion Primary tracheal tumors should be highly suspected in patients with recurrent and gradually worsening dyspnea; timely cervical, thoracic CT and bronchoscopy can provide an accurate diagnosis. Surgical radical resection is the only way to cure all benign tracheal tumors such as lipoma.
Keywords: surgical treatment; tracheal lipoma; bronchoscopy; tracheal stent